Comunidade bacteriana do solo e seu potencial biotecnológico sob sistemas integrados no ecótono Cerrado Amazônia - Carmo, Kellen Banhos do (2015)
Integrated production systems have been suggested as alternative to sustainable land use. The objective of this study was to evaluate integrated agricultural production systems through the occurrence of bacterial soil communities in a transition area of Cerrado and Amazon rainforest, beyond to bioprospect bacteria with potencial to solubilize phosphorus and be antagonistic to plant pathogens. The experimental belongs to Embrapa Agrosilvopastoral (Sinop /MT) and were evaluated three monoculture systems (planted forest of eucalyptus, Crop and Pasture) and seven integrated systems (IL-P, IP-L, ILF, IPF, ILF-IPF , IPF-ILF, ILPF) arranged in four blocks plus Native forest and Fallow as areas of references. Soil samples were collected at depth 0-10 cm in the rainy and dry season in 2012. It had been determined the number of colony forming units (CFUs) and potencial antagonistic and to solubilize phosphorus in culture medium with CaHPO4. The structure and composition of the soil bacterial community were assessed by denaturing gradient gel electrophoresis (DGGE) and sequencing. The highest CFU was in the integrated system during the rainy season. By orthogonal contrasts, the ILPF was responsible to make difference compared at the other integrated systems with a probability of 3%. In the rain, both references areas had lower CFU and the Fallow differed among five treatments. The DGGE analysis grouped in both seasons the exclusive systems with each other and separately the ILPF with the references areas. In the rain, 12.08% bacterial isolates controlled the pathogens (Rhizoctina sp., Fusarium sp., Sclerotium rolfsii) and 20.83% in the dry season. The same isolates evaluated in antagonism, 56.25% solubilized phosphate in the rainy season and 47.08% dry. The bacteria with biotechnological potential were classified as phyla Firmicutes, Actinobacteria, Proteobacteria and Nitrospira being represented by nine genera and 14 species. The result in the sequencing performed into seven treatments (Forest, Crop, Grassland, ILF, IPF, ILPF and Native) showed the greatest abundance to the same first three phyla obtained in the biotechnological potential in both seasons. The Firmicutes correlated with the Crop in the rainy period and with ILPF and Native in the dry. For five classes corresponding to the three phyla, the Crop stood out with the greatest fluctuations in their relative abundance compared to other treatments. In cluster analysis by gender in the rain, only the Forest and the ILPF had no similarity with the other treatments but in the dry the two were grouped with the Forest and IPF. Therefore, the bacterial community in the soil integrated systems was sensitive to management systems with only two years of experimental deployment. The ILPF showed the greatest similarity of bacterial structure with the Native forest. The Crop showed the highest fluctuations in the relative abundance of the two seasons, being more susceptible to treatment changes in microbial composition of the soil. The transition area between the Cerrado and Amazon is promising in bioprospecting bacteria with the biotechnological potential pathogens and phosphorus solubilization.